2017
DOI: 10.1016/j.neuroimage.2017.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging of auditory cortical fields in awake marmosets

Abstract: The primate auditory cortex is organized into a network of anatomically and functionally distinct processing fields. Because of its tonotopic properties, the auditory core has been the main target of neurophysiological studies ranging from sensory encoding to perceptual decision-making. By comparison, the auditory belt has been less extensively studied, in part due to the fact that neurons in the belt areas prefer more complex stimuli and integrate over a wider frequency range than neurons in the core, which p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…However, the lissencephalic brain of the marmoset provides convenience to study primary and high-order auditory cortices ( Okano and Mitra, 2015 ). While most of the previous marmoset studies were limited to electrophysiological techniques and mainly focused on auditory calls and pitch processing ( Bendor and Wang, 2005 ; Bendor and Wang, 2008 ; Toarmino et al, 2017 ; Zhou and Wang, 2012 ), the present study has begun to examine the auditory sequences at the whole-brain level. In particular, we revealed that both prediction-error and prediction-updating signals are located in the core and belt regions of the auditory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lissencephalic brain of the marmoset provides convenience to study primary and high-order auditory cortices ( Okano and Mitra, 2015 ). While most of the previous marmoset studies were limited to electrophysiological techniques and mainly focused on auditory calls and pitch processing ( Bendor and Wang, 2005 ; Bendor and Wang, 2008 ; Toarmino et al, 2017 ; Zhou and Wang, 2012 ), the present study has begun to examine the auditory sequences at the whole-brain level. In particular, we revealed that both prediction-error and prediction-updating signals are located in the core and belt regions of the auditory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Chimpanzees show rightward lateralization for at least some communication calls (Taglialatela et al, 2009), and macaques have dedicated voice selective cells and regions primarily in the right anterior temporal lobe (‘voice patches’, Perrodin et al, 2011; Petkov et al, 2008). Although these higher order regions may be in different locations with respect to lower level AC in different primate species, the same principle of abstraction of incoming stimuli along the auditory processing hierarchy holds in non‐human primates (Belin et al, 2018; Romanski & Averbeck, 2009; Sadagopan & Wang, 2009; Toarmino et al, 2017; Zhu et al, 2019b) and humans (Humphries et al, 2014; Latinus et al, 2013; Pernet et al, 2015; Tremblay et al, 2013).…”
Section: Basic Acoustic Features and Their Cortical Processing In Mam...mentioning
confidence: 99%
“…Due to the difficulty of scanning NHP subjects while they are awake, and the requirement that subjects remain still during the scanning session, task-related fMRI in NHP is rare and most studies have focused on perceptual tasks in two or three subjects (e.g. Poirier et al., 2017 ; Toarmino et al., 2017 ; Clery et al., 2018 ). To understand inter-subject variability, the most promising approach is to correlate inter-individual differences in brain structure and function at rest with behaviour measured outside the scanner.…”
Section: Behavioural Phenotyping Datamentioning
confidence: 99%